2013
DOI: 10.1117/1.jbo.18.8.087004
|View full text |Cite|
|
Sign up to set email alerts
|

Correlating the amount of urea, creatinine, and glucose in urine from patients with diabetes mellitus and hypertension with the risk of developing renal lesions by means of Raman spectroscopy and principal component analysis

Abstract: Abstract. Patients with diabetes mellitus and hypertension (HT) diseases are predisposed to kidney diseases. The objective of this study was to identify potential biomarkers in the urine of diabetic and hypertensive patients through Raman spectroscopy in order to predict the evolution to complications and kidney failure. Urine samples were collected from control subjects (CTR) and patients with diabetes and HT with no complications (lower risk, LR), high degree of complications (higher risk, HR), and doing blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 27 publications
2
72
0
1
Order By: Relevance
“…The Raman spectrum of serum in this study (Figure 2) presented features consistent with the Raman spectrum of glucose; the peaks at 507, 1065 and 1128 cm -1 were similar to those described by Bispo et al (2013) Figure 8. Plot of the first five PCA loading vectors (LV) with positive as well as negative peaks in the same positions of the indicated biochemical elements.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The Raman spectrum of serum in this study (Figure 2) presented features consistent with the Raman spectrum of glucose; the peaks at 507, 1065 and 1128 cm -1 were similar to those described by Bispo et al (2013) Figure 8. Plot of the first five PCA loading vectors (LV) with positive as well as negative peaks in the same positions of the indicated biochemical elements.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on urine have demonstrated identification and quantification, by means of Raman analysis, of selected parameters important for diagnostics of kidney disease (Bispo et al, 2013;Dou et al, 1996;McMurdy and Berger, 2003). Serological analysis aimed at diagnosis of hepatitis C has also successfully been performed using Raman analysis (Saade et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of FTIR and Raman spectroscopy has been widely investigated for diagnostic purposes for cell and tissue analysis and the feasibility to use them for serum sensing has been suggested and applied to a wide range of body fluids [53] ranging from serum [54][55][56][57], tears [58] urine or saliva [59][60][61]. In both Infrared and Raman spectroscopic studies, to date the analysis has predominantly been performed on air dried drops of serum deposited on spectroscopically neutral substrates such as CaF 2 [62,63] .…”
Section: Biophotonicsmentioning
confidence: 99%
“…This enables analysis to be done in each sample collected during the day, increasing the ease of analysis and patient comfort both of which may lead to more accurate results [79]. Raman spectroscopy has been shown to be applicable to this with studies now available suggesting a role in the detection of biomarkers in the urine of diabetic patients with renal impairment that may lead to earlier diagnosis of this complication and better management [80]. Urine samples were collected from control subjects vs. patients with diabetes and hypertension in the absence of complications, a high degree of complications and those requiring renal dialysis.…”
Section: Diabetesmentioning
confidence: 99%